일부 성인에서 치주질환 자각증상과 삶의 질의 관련성 - 이미라; Mi Ra Lee; 최준선; Jun Seon Choi (Chiwisaeng gwahakoeji, 2012)
The aim of this study was to investigate the correlations between the self-reported symptoms of periodontal diseases and the quality of life. This study conducted its questionnaire survey over the subjects of 450 adults who had ever visited dental clinics among the adults of age 35-65 living in Seoul and Gyeonggi-do region from January 7 to March 14, 2010. The data were analyzed using a chi-square test, t-test, binominal logistic regression analysis in the SPSS version 12.0 program. Among the self-reported symptoms of periodontal diseases, 65% of respondents perceived that ``I bleed from the gums in brushing my teeth``, which was the most, whereas 18.8% of respondents perceived to ``tooth mobility``, which was the least. Self-reported symptoms of periodontal diseases was associated with socio-demographic characteristics such as sex, age, level of education and periodic oral examination, dental scaling(p<0.05). People who perceived the symptoms of periodontal diseases experienced functional limitation, physical pain, psychological discomfort, disability in diverse domains, and social handicap more than the group who did not perceive them(p<0.001). OHIP-14 scores were significantly correlated with sex, bleeding gums, swollen gums and bad breath(p<0.05). This study showed the self-reported periodontal problem had a negative impact on the public`s leading their happy life. Therefore, in order to enhance the quality of life in adults, it is necessary to prevent periodontal diseases and reduce the subjective symptoms.